Antidiabetic potential of Conocarpus lancifolius - Saadullah, Malik; Chaudary, Bashir Ahmad; Uzair, Muhammad; Afzal, Khurram (Bangladesh Journal of Pharmacology, 2014)
The antidiabetic activity of Conocarpus lancifolius extract was investigated in vitro, as alpha glucosidase inhibition and in vivo as alloxan induced diabetic rabbits with other biochemical parameters (LDL, HDL, SGPT, SGOT, cretinine, urea and triglyceride). Alpha-glucosidase inhibition activity was performed by using acorbose as standred. Methanolic extract show alpha-glucosidase inhibition activity. The dose of 200 mg/kg body weight significantly (p<0.05) decreases the blood glucose level, plasma total cholesterol, triglycerides and LDL in treated rabbits as compared to diabetic rabbits. This dose significantly increased the level of HDL in treated group. The activity of SGOT and SGPT also significantly (p<0.05) decreased in treated diabetic rabbits. Phytochemical studies show the presence of glycosides, tannins, saponins and terpenoids. The antidiabetic potential is may be due to its saponin contents.